Design and Build a System for Turning on an IoT-Based Motorcycle Starter Using Voice - Muhammad Alfanny; Achmad Fauzi; Hermansyah Sembiring (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Motorcycles require maintenance, especially on the engine, by always heating the motorcycle before use or when not in use. However, sometimes someone is lazy to warm up the motorcycle engine. The aim is to make it easier for users to warm up the motorcycle engine to avoid damage to the engine and make it easier for motorcycle users if the electric starter on the motorbike is damaged. Research using the IoT-based google assistant uses NodeMCU 8266 connected to an Android smartphone to start motorbikes automatically. Based on the research results this tool can function properly. The conclusion of the study is that the motorcycle starter system with a smartphone control system can avoid damage to the motorcycle engine, and makes it easier for users to start the motorcycle if the electric starter is damaged.